Elements of security and non-proliferation - Jalouneix, Jean (EDP SCIENCES, 2017)
Following on from the work on the safety of nuclear facility published in 1996, which needed to be updated and extended in scope, IRSN has created a new series of educational publications entitled "Elements of nuclear safety, radiological protection and security". The series takes up the general objective of tackling all aspects of risk management in the nuclear field, in terms of protecting human health, society and the environment. The first publication in this series, covering nuclear security and non-proliferation, describes the measures implemented in France and at international level to prevent terrorism and malicious acts and, if necessary, mitigate the consequences of any such act. It deals with the security of nuclear material, nuclear facilities and the transport of nuclear material, the security of radioactive sources and describes States' undertakings to implement safeguards relative to tracking nuclear material and chemicals to prevent their use for fraudulent purposes. These publications will be of interest to anyone concerned by these issues, especially those who work in the nuclear industry, but it will also answer many questions that members of the public may have regarding these subjects. It indudes information on context and history, the provisions and requirements contained in French regulations and international agreements, as well as details of the roles played by the various entities involved, induding IRSN.